Characteristics and Comparison of Adverse Events of Coronavirus Disease 2019 Vaccines Reported to the United States Vaccine Adverse Event Reporting System Between 14 December 2020 and 8 October 2021 - Zou, Chenyu; Xue, Xiangzhong; Qian, Jingjing (Frontiers in Medicine, 2022)
Background: This study assessed and compared the frequency and type of adverse events (AEs) of the Pfizer-BioNTech, Moderna, and Janssen COVID-19 vaccines reported in the Vaccine Adverse Event Reporting System (VAERS). Methods: A retrospective analysis examined VAERS reports between Dec-14, 2020, and Oct-8, 2021 and focused on AE reports related to COVID-19 vaccines and AE outcomes (emergency room (ER) visits after being vaccinated, hospitalization, prolongation of existing hospitalization, life-threatening events, disability, birth defect, and death). Reporting odds ratios (RORs) and Breslow-Day statistics were used to compare AE reporting between COVID-19 and non-COVID vaccines and between individual COVID-19 vaccines. Results: A total of 604,157 AEs of COVID-19 vaccines were reported, including 43.51% for Pfizer-BioNTech, 47.13% for Moderna, and 9.12% for Janssen COVID-19 vaccine. About 12.56% of patients visited ER after being vaccinated, 5.96% reported hospitalization, and 1.52% reported life-threatening events. Among the death cases (n=7,674; mean age=73), 2,025 (26.39%) had hypertension and 1,237 (16.12%) had cancer. RORs between COVID-19 vaccines versus non-COVID vaccines identified increased reporting odds in ER visits, hospitalization, and life-threatening events. The results of the Breslow-Day statistics indicated heterogeneities between the disproportionality of reports across the four serious AE outcomes (ER visits, hospitalization, life-threatening events, and disability) between individual COVID-19 vaccines. Conclusions: Most current VAERS reports showed that most commonly reported AEs of COVID-19 vaccines were mild. Cases with a mortality outcome tended to occur in older adults with underneath conditions. Close ongoing surveillance in safety of COVID-19 vaccines is critical and will inform the use of individual COVID-19 vaccines. Given the known limitations associated with the passive spontaneous reporting system such as VAERS, our findings need to be further assessed and verified through longitudinal, large healthcare data systems.